Contagion in dealer networks - Jean-Sébastien Fontaine; Adrian Walton (Bank of Canada, 2020)
Dealer networks provide essential intermediation services in over-the-counter markets. We document the response of dealer networks to the arrival of new public information. We find that after public news releases, dealer networks become more complex and channel larger flows of securities between buyers and sellers. These effects are concentrated in bonds that were more actively traded and had more-complex dealer networks. One natural interpretation is that dealer networks become more complex after the news releases to accommodate shifts of intermediation demand. For these bonds, following the news releases, we also document more frequent and larger contagion of settlement fails over the network. The evidence points to a trade-off. Settlement fails allow for contagion of counterparty risk in dealer networks; yet, allowing for fails provides dealers greater flexibility to accommodate shifts in demand for intermediation.
Keywords: E4; G1; G2; G21; L1; L14; 330; Financial markets; Payment clearing and settlement systems; Market structure and pricing